High-Density Genetic Linkage Mapping of Lepidium Based on Genotyping-by-Sequencing SNPs and Segregating Contig Tag Haplotypes - Geleta, Mulatu; Gustafsson, Cecilia; Glaubitz, Jeffrey C.; Ortiz, Rodomiro (Frontiers in Plant Science, 2020)
Lepidium campestre has been targeted for domestication as future oilseed and catch crop. 380 plants comprising genotypes of L. campestre, L. heterophyllum and their interspecific F2 mapping population were genotyped using genotyping by sequencing (GBS), and the generated polymorphic markers were used for the construction of high-density genetic linkage map. TASSEL-GBS, a reference genome-based pipeline, was used for this analysis using a draft L. campestre whole genome sequence. The analysis resulted in 120438 biallelic single nucleotide polymorphisms (SNPs) with minor allele frequency (MAF) above 0.01. The construction of genetic linkage map was conducted using MSTMap based on phased SNPs segregating in 1:2:1 ratio for the F2 individuals, followed by genetic mapping of segregating contig tag haplotypes as dominant markers against the linkage map. The final linkage map consisted of eight linkage groups (LGs) containing 2330 SNP markers, and spanned 881 Kosambi cM. 10302 contigs were genetically mapped to the eight LGs, which were assembled into pseudo-molecules that covered a total of ca 120.6 Mbp. The final size of the pseudo-molecules ranged from 9.4 Mbp (LG-4) to 20.4 Mpb (LG-7). The following major correspondence between the eight Lepidium LGs (LG-1 to LG-8) and the five Arabidopsis thaliana (At) chromosomes (Atx-1 to Atx-5) was revealed through comparative genomics analysis: LG-1&2_Atx-1, LG-3_Atx-2&3, LG-4_Atx-2, LG-5_Atx-2&Atx-3, LG-6_Atx-4&5, LG-7_Atx-4, and LG-8_Atx-5. This analysis revealed that at least 66% of the sequences of the LGs showed high collinearity with At chromosomes. The sequence identity between the corresponding regions of the LGs and At chromosomes ranged from 80.6% (LG-6) to 86.4% (LG-8) with overall mean of 82.9%. The map positions on Lepidium LGs of the homologues of 24 genes that regulate various traits in A. thaliana were also identified. The eight LGs revealed in this study confirm the previously reported (1) haploid chromosome number of eight in L. campestre and L. heterophyllum; (2) chromosomal fusion, translocation and inversion events during the evolution of n=8 karyotype in ancestral species shared by Lepidium and Arabidopsis to n=5 karyotype in A. thaliana. This study generated highly useful genomic tools and resources for Lepidium that can be used to accelerate its domestication.